Experimental Study of Friction Coefficient and Wear Rate of Turned and Ground Mild Steel Surfaces Sliding Against Smooth and Rough SS304 Counterfaces - Nuruzzaman, D. M.; Chowdhury, M. A.; Chowdhury, M. A. K.; Roy, B. K. (Institution of Engineers Australia, 2014)
A series of experimental tests were carried out using turned and ground mild steel surfaces rubbing against smooth and rough stainless steel 304 (SS304) conterfaces under different operating conditions on a pin-on-disc test rig. During testing, the friction coefficient and wear rate were recorded. The topography of worn surfaces was also observed with optical microscope. The average surface roughness of turned and ground mild steel were measured after friction test. The result displays that normal load, sliding speed and the surface conditions of sliding pairs have a distinct effect on the friction and wear behaviour of turned and ground mild steel rubbing against smooth and rough SS304 conterfaces. During this study, the effects of duration of rubbing on friction coefficient are also observed. Friction coeffi cient and wear rate of four types of disc-pin combinations such as ground-smooth, turned-smooth, ground-rough and turned-rough are observed under different normal loads and sliding velocities. Experimental results reveal that friction coefficient of mild steel for all types of disc-pin combinations decreases with the increase in normal load and sliding velocity.